Pengaruh Citra Merek, Kualitas Produk, Dan Pengalaman Pelanggan Terhadap Keputusan Pembelian Noera Collagen Drink Di Tiktok - Miftachul Hasanah S; M Khoiri (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to investigate the influence of brand image, product quality and customer experience on purchasing decisions for Noera Collagen Drink on TikTok. The population of this research is the people of Sagulung, Batam City who use Noera Collagent Drink products in 2023, the exact number of which is not known. The sampling technique used the Jacob Cohen formula, which resulted in 204 respondents who were selected deliberately. The data analysis process involves a series of steps, including data quality testing, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis show that brand image has an influence of 35.5% on purchasing decisions. Product quality has an influence of 20.7% on purchasing decisions. Customer experience has an influence of 35.8% on purchasing decisions. Analysis of the coefficient of determination (R2) confirms that overall brand image, product quality and customer experience are able to explain 53.3% of the variation in purchasing decisions. The results of the t test and F test confirm that brand image, product quality and customer experience have a positive and significant influence, both partially and simultaneously on the decision to purchase Noera Collagen Drink on TikTok.